The Concept of Political Culture - Welch, Stephen. author. aut Link
IX, 208 p.
Keywords: '...erudite, thought-provoking and well-written.'Archie Brown, Professor of Politics, Oxford University. The return to prominence of the concept of political culture offers an opportunity to re-evaluate its contribution to the social sciences. This study casts a broader than usual net, embracing not only political science (with equal emphasis placed on the concept's use in communist studies), but also sociology and history. On this basis a distinctive theory of political culture, and not merely another typology, is developed. Political culture, instead of being a token in the sterile debate between interest- and culture-based explanation, offers the means of transcending that debate.